Mapping the Research on Health Policy and Services in the Last Decade (2009–2018): A Bibliometric Analysis - Zhao, Linyan; Zhao, Yang; Du, Jian; Desloge, Allissa; Hu, Zhiyong; Cao, Gaofang (Frontiers in Public Health, 2022)
Background Health policy and services is a continuously evolving field of research that can inform prevention and control efforts for a variety of health conditions. The “Healthy China” strategy reflects the demand to formulate health policy that suits China's national needs and goals. Applying bibliometric analysis to grasp the general situation of health policy and services research globally will be conducive to informing China's designated health plans and initiatives. Method A bibliometric analysis of 58,065 articles on “Health Policy and Services” topics was conducted. The document type was restricted to journal articles that were published in the Web of Science database between the time parameter of January 1, 2009 to December 31, 2018. Data was collected on indicators such as the annual number of publications in the field of health policy and services, the country where the publication is issued, the publication organization, the source journal, the frequency of citations, research hotspots, and academic areas. Results The overall number of articles published in Web of Science on health policy and services research has increased over time. The United States has the largest number of articles in the field. The institution with the highest number of citations in the field is Harvard University and the journal with the most published articles in the field is Health Affairs. Research hotspots in the health policy and services field include topics such as “HIV Infections,” “Primary Health Care,” “Delivery of Health Care,” and “Health Services Accessibility.” Conclusion Experts in the field of health policy and services globally are dedicated to researching the most effective ways to improve people's health and living standards. There is a certain gap in the depth of health policy and services research between China and developed countries and regions such as Europe or America. China must learn from foreign experience to conduct meaningful and informative research that can aid in the formulation of multi-dimensional health policies in specific areas such as environmental infectious diseases, where attention is needed in areas beyond the medical and health system.